Development of speech and thinking in children (Zien Journal of Social Sciences and Humanities, 2022)
The author of the article does not have the opportunity to think from birth. He introduced the concept of the introduction of technology in all spheres, the need for the development of all psychological processes in humans and children, first of all, the development of thinking, and a number of features.